2015
DOI: 10.1007/s40489-015-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Point-of-View Video Modeling as a Social Skills Intervention for Children with Autism Spectrum Disorders

Abstract: Distinguishing characteristics of individuals with autism spectrum disorder (ASD) are deficits in social communication and interaction. Point-of-view video modeling has the potential to address these deficits. Therefore, the literature review investigated research targeting social skills through the application of point-of-view video modeling. Both electronic and ancestral searches of the literature yielded five pertinent studies, which included research conducted from 2006 to 2012, and included participants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
(63 reference statements)
0
7
0
1
Order By: Relevance
“…A comprehensive review of the literature conducted by Lee (2015) found the application of point-of-view VM to teach social interaction and communication to be limited, but promising. Hine and Wolery (2006) investigated whether point-of-view VM could be used to teach appropriate play with two toy sets (i.e., gardening and cooking) containing various items.…”
mentioning
confidence: 99%
“…A comprehensive review of the literature conducted by Lee (2015) found the application of point-of-view VM to teach social interaction and communication to be limited, but promising. Hine and Wolery (2006) investigated whether point-of-view VM could be used to teach appropriate play with two toy sets (i.e., gardening and cooking) containing various items.…”
mentioning
confidence: 99%
“…According to Walker [21], social skills are a set of competencies that: a) allow an individual to initiate and maintain positive social relationships, b) contribute to peer acceptance and to a satisfactory school adjustment, and c) allow an individual to cope effectively with the larger social environment.…”
Section: Resultsmentioning
confidence: 99%
“…A third limitation occurred due to the individualised nature of the FFVSM intervention, which meant it was not possible to control some confounding variables across participants, including the length of the video, and the speed of words read correctly per minute during the self-model. A literature review discussed that video length may affect the level of attending for individuals with ASD (Lee, 2015 ), but suggested more research is required to explain these findings. Video models were also only watched once per session during the present research; although this was adequate for producing improvements for some participants, research has shown that multiple viewings may be more beneficial for students with ASD (Wert & Neisworth, 2003 ; Wang & Koyama, 2014 ).…”
Section: Discussionmentioning
confidence: 99%